The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1088/0954-3899/34/7/s07
|View full text |Cite
|
Sign up to set email alerts
|

Hadron spectroscopy: theory and experiment

Abstract: Many new results on hadron spectra have been appearing in the past few years thanks to improved experimental techniques and searches in new channels. New theoretical techniques including refined methods of lattice QCD have kept pace with these developments. Much has been learned about states made of both light (u, d, and s) and heavy (c, b) quarks. The present review treats light-quark mesons, glueballs, hybrids, particles with a single c or b quark, charmonium (cc), and bottomonium (bb) states. Some prospects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 218 publications
7
112
0
Order By: Relevance
“…[27], which is consistent with the theoretical calculations in Refs. [4,5,10,[41][42][43][44]. In recent years, many other experiments have reported D * 2 (2460) [2, 25, 28-31, 33-37, 39, 40, 45].…”
Section: Status Of the Observed Charmed Mesonsmentioning
confidence: 99%
“…[27], which is consistent with the theoretical calculations in Refs. [4,5,10,[41][42][43][44]. In recent years, many other experiments have reported D * 2 (2460) [2, 25, 28-31, 33-37, 39, 40, 45].…”
Section: Status Of the Observed Charmed Mesonsmentioning
confidence: 99%
“…These different theoretical states may offer explanations for differences in decay rates and decay modes, but the current theoretical and experimental information is not definitive enough to assign quantum numbers to any of the new excited charm-strange states. Some authors have argued that the c 2980 is a 1=2 state [8] and that the c 3077 is a 5=2 state [8,9]; however, other J P assignments are not ruled out. Future experimental studies of these and other states and decay modes, and further theoretical work, will help to clarify the properties of these new charm-strange baryons.…”
Section: Invariantmentioning
confidence: 99%
“…Several excited charm-strange baryons with J P f1=2 ; 3=2 g are predicted, with masses ranging from about 2800 MeV=c 2 to 3150 MeV=c 2 [6,7]. Other authors [8][9][10] consider J P 5=2 states and radial excitations, and use the measured natural widths and decay modes in assigning possible quantum numbers for the new c 2980 ;0 and c 3077 ;0 states. In this paper, we report measurements of excited charmstrange baryon properties based on a data sample corresponding to an integrated luminosity of 384 fb ÿ1 recorded with the BABAR detector at the PEP-II asymmetric-energy e e ÿ storage rings at the Stanford Linear Accelerator Center.…”
Section: Introductionmentioning
confidence: 99%
“…This initiated great interests in the heavy flavor baryon spectrum in both experiment and theory. At present, the experimental information is still limited and nearly nothing is known for their spin-parity quantum numbers (some review of the charmed baryons can be found in [5][6][7][8]). How to understand the properties of these new charmed baryons, e.g.…”
Section: Introductionmentioning
confidence: 99%